2001
DOI: 10.1523/jneurosci.21-02-00691.2001
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition in Rat Superior Colliculus Mediated by GABACReceptors

Abstract: The stratum griseum superficiale (SGS) of the superior colliculus contains a high concentration of the recently described GABA C receptor. In a previous study, it was postulated that activation of these receptors on inhibitory interneurons functions to disinhibit projection cells that relay visual information to the thalamus and brainstem. To test this model, we used in vitro whole-cell patch-clamp methods to measure effects of GABA and muscimol on EPSCs and IPSCs evoked in rat SGS by electrical optic layer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 45 publications
5
81
2
Order By: Relevance
“…However, the superficial layers of the SC contain a wide variety of cell types, including interneurons and cells that project to the parabigeminal nucleus, contralateral SC, pretectum, ventral and dorsal lateral geniculate nuclei, and lateral posterior nucleus (for reviews, see Huerta and Harting, 1984;May, 2006). SC interneurons, tectopretectal, and tectotectal neurons have been found to be GABAergic (Appell and Behan, 1990;Mize, 1992;Schmidt et al, 2001, Baldauf et al, 2003. Thus, these cell types may be ruled out as the primary targets of area 17 terminals.…”
Section: Postsynaptic Targets Of Cortical Terminalsmentioning
confidence: 99%
“…However, the superficial layers of the SC contain a wide variety of cell types, including interneurons and cells that project to the parabigeminal nucleus, contralateral SC, pretectum, ventral and dorsal lateral geniculate nuclei, and lateral posterior nucleus (for reviews, see Huerta and Harting, 1984;May, 2006). SC interneurons, tectopretectal, and tectotectal neurons have been found to be GABAergic (Appell and Behan, 1990;Mize, 1992;Schmidt et al, 2001, Baldauf et al, 2003. Thus, these cell types may be ruled out as the primary targets of area 17 terminals.…”
Section: Postsynaptic Targets Of Cortical Terminalsmentioning
confidence: 99%
“…However, unlike in the retina (McCall et al, 2002), synaptic currents through GABA C receptors were rarely observed in the sSC under normal conditions (Boller and Schmidt, 2003). Additionally, activation of GABA C receptors in the sSC results in disinhibition (Schmidt et al, 2001), suggesting that GABA C receptor blockade might reduce ON activity and augment the pause. Thus, although we did not examine the effect of GABA C receptor blockade, it could be speculated that the contribution of GABA C receptors in the generation and modulation of the ON and pause responses might be minor compared to that of GABA A and GABA B receptors.…”
mentioning
confidence: 95%
“…However, because we did not test the effects of juxtasomal current injection on these pharmacologically manipulated neurons, we cannot exclude the possibility that the pause in these neurons might be attributable to a pause of retinal ganglion cells. An alternative candidate might be GABA C receptor-mediated inhibition given that GABA C receptors are reportedly expressed in the sSC (Schmidt et al, 2001;Boller and Schmidt, 2003;Kirischuk et al, 2003). However, unlike in the retina (McCall et al, 2002), synaptic currents through GABA C receptors were rarely observed in the sSC under normal conditions (Boller and Schmidt, 2003).…”
mentioning
confidence: 99%
“…The circuits that organize this activity have been studied in vitro in slice preparations (for review, see Isa and Saito, 2001;Grantyn et al, 1984;Lee et al, 1997Lee et al, , 2007Isa et al, 1998;Meredith and Ramoa, 1998;Lo and Mize, 2000;Schmidt et al, 2001;Isa, 2002;Isa and Sparks, 2006;Neale and Salt, 2006;Kaneda et al, 2008). Furthermore, profiles of field potential responses at different depths evoked by sSC stimulation were measured by single-electrode recordings in anesthetized rats (Katsuta and Isa, 2003) and monkeys (Nikitin and Isa, 2004).…”
Section: Introductionmentioning
confidence: 99%